Environment and Natural Resource Conservation and Management in Mozambique - Mawere, Munyaradzi (Book collections on Project MUSE., 2013)
This is an eloquent, engaged and extremely well informed narrative of the environmental and natural resource conservation and management issues in Mozambique. While the topics in this volume are diverse, they are all explicitly designed to move beyond the routinized blame of natural resource mismanagement and environmental degradation on local communities, and to rethink ecosystem destruction, land degradation and natural resource over-exploitation in Africa and beyond. Never losing sight of the major causes of environment and resource mismanagement in Mozambique, the book advances the thesis.